Effect of surfactants on the formation of oil-wicking aqueous gel for the remediation of oil spilled into surface water. (15th March 2021) - Walls, Daniel J.; Espitalié, Emilie; Hum, Gabriel; Chen, Jun; Gattrell, Michael; Li, Anwu; Frostad, John M.
Highlights: The reported self-assembling aqueous gel absorbs oil through capillary forces. Control of microstructure with surfactant modifies macroscopic properties of gel. Surfactants influenced gelation in ways not entirely predicted by current theory. Under compression, gel exhibited stress-strain relation similar to cellular solids. Optimizing mechanical strength and rate of oil absorption feasible. Abstract: We report an investigation into how to tune an aqueous gel formed from a low molecular weight gelator for absorbing spilled oil. We conducted a systematic study of the effects of four separate surfactants on the formation of the gel and its compressive strength and oil absorption. Our experiments showed that the gelator can form an aqueous gel in the presence of each surfactant. Subjected to a normal compression force, the gels exhibit compressive stress-strain relationships similar to cellular solids. Higher concentrations of surfactant increase the stress response. Shear measurements during the formation of the gels indicated that the influence of surfactant on the growing gel is more complex than predicted by crystallographic mismatching. Wicking experiments indicated that surfactant influenced the pore size formed in the gels. Values of dimensional growth of the gel network and wicking rates both diverged with increasing concentration of surfactant across the four surfactants.